Molybdenum cofactor in chlorate-resistant and nitrate reductase-deficient insertion mutants of Escherichia coli. - Miller, J B (1983)
We examined molybdenum cofactor activity in chlorate-resistant (chl) and nitrate reductase-deficient (nar) insertion mutants and wild-type strains of Escherichia coli K-12. The bacterial molybdenum cofactor was assayed by its ability to restore activity to the cofactor-deficient nitrate reductase found in the nit-1 strain of Neurospora crassa. In the wild-type E. coli strains, molybdenum cofactor was synthesized constitutively and found in both cytoplasmic and membrane fractions. Cofactor was found in two forms: the demolybdo form required additional molybdate in the assay mix for detection, whereas the molybdenum-containing form was active without additional molybdate. The chlA and chlE mutants had no detectable cofactor. The chlB and the narG, narI, narK, and narL (previously designated chlC) strains had cofactor levels similar to those of the wild-type strains, except the chlB strains had two to threefold more membrane-bound cofactor. Cofactor levels in the chlD and chlG strains were sensitive to molybdate. When grown in 1 microM molybdate, the chlD strains had only 15 to 20% of the wild-type levels of the demolybdo and molybdenum-containing forms of the cofactor. In contrast, the chlG strains had near wild-type levels of demolybdo cofactor when grown in 1 microM molybdate, but none of the molybdenum-containing form of the cofactor. Near wild-type levels of both forms of the cofactor were restored to the chlD and chlG strains by growth in 1 mM molybdate.